L’atelier de méthodes de Sciences Po : apprendre, aider, rassembler - Diégo Antolinos-Basso; Audrey Baneyx; Héloïse Théro; Benjamin Ooghe-Tabanou; Paul Girard (Humanités Numériques)
The digital turn is changing our society, and the production of knowledge in the humanities and social sciences. To disseminate their expertise in digital methods, research engineers at Sciences Po created in 2013 a monthly methods workshop open to everyone: the METAT. The participants (researchers, students and others) sign up for a 3-hour session, and present their issue – which can be technical or methodological – to a team of supervisors from diverse backgrounds and profiles providing support that is as individualised as possible. In this article, we will explain the organisation and founding values of the METAT, as well as give our feedback as supervisors and organisers. This description will be enriched with the analysis of data built from the reports and registration form. We hope this article can give teachers in the humanities and social sciences information on the growing demand for digital training, provide feedback on a project-based digital teaching, and maybe inspire other organisations to create their own methods workshop.